Onset of major Pleistocene glaciations in the Alps - G. Muttoni; C. Carcano; E. Garzanti; M. Ghielmi; A. Piccin; R. Pini; S. Rogledi; D. Sciunnach (2003)
Since alligators patrolled Greenland swamps in the Eocene, the Earth's climate underwent significant cooling, which culminated in the Pleistocene Ice Age with recurring glaciations in vast regions of the Alps, Eurasia and North America, and overgrowth of polar icecaps in Antarctica and Greenland. During main Pleistocene glacial penetrations, the Alpine icecap invaded the low gradients of the Central Europe uplands and Italian Po plain. Peri-glacial sedimentary basins such as the Po Basin are natural collectors of past biological and climatic changes involving the waxing and waning of major icecaps. We have found in a 200m-thick core from the central Po plain near Milan stratigraphic evidence for a major glacial pulsation of the nearby Alpine icecap, which occurred in correspondence of a seismically traceable unconformity of regional relevance, termed the "Red Unconformity" (RU) in Eni/Agip terminology. The RU is associated with a major reorganization of vegetation cover and Alpine drainage pattern. The age of the RU was constrained magnetostratigraphically to the the first major Pleistocene glacio-eustatic lowstand at 0.87Ma (Oxygen Isotope Stage 22). This corresponds to the end of the "Mid Pleistocene Revolution" (MPR), a marked reorganization of northern hemisphere glaciation pattern which took place in the late Early Pleistocene. We suggest that the MPR/MIS 22 was associated with the onset of the first major Pleistocene glaciation in the Alps. Noticing the similarity in number of major Pleistocene glacieustatic low-stands starting with MIS 22, and the four-fold Alpine glacial subdivision of Penck and Brückner (1909), we conclude that "Penck and Brückner in 1909 may not have been, after all, that wrong" (Kukla and Cilek, 1996).